Software for muscle fibre type classification and analysis - Karen, P; Stevanec, M; Smerdu, V; Cvetko, E; Kubínová, L; Erzen, I (European journal of histochemistry, 2009)
Fibre type determination requires a large series of differently stained muscle sections. The manual identification of individual fibres through the series is tedious and time consuming. This paper presents a software that enables (i) adjusting the position of individual fibres through a series of differently stained sections (image registration) and identification of individual fibres through the series as well as (ii) muscle fibre classification and (iii) quantitative analysis. The data output of the system is the following: numerical and areal proportions of fibre types, fibre type size and optical density (grey level) of the final reaction product in every fibre. The muscle fibre type can be determined stepwise, based on one set of stained sections while further, newly stained sections can be added to the already defined muscle fibre profile. Several advantages of the presented software application in skeletal muscle research are presented. The system is semiquantitative, flexible, and user friendly.
Keywords: Software; kosterní svalová vlákna; software; Muscle Fibers, Skeletal; Humans; In Situ Hybridization; hybridizace in situ; krysa rodu Rattus; lidé; zvířata; Immunohistochemistry; těžké řetězce myosinu; Myosin Heavy Chains; počítačové zpracování obrazu; imunohistochemie; Image Processing, Computer-Assisted; reprodukovatelnost výsledků; protein - isoformy; Protein Isoforms; musculus masseter; Reproducibility of Results; User-Computer Interface; uživatelské rozhraní počítače; Myosins; myosiny; Rats; Animals; Masseter Muscle